PENINGKATAN KETERAMPILAN MENULIS PERMULAAN MELALUI MEDIA MANIPULATIF: KARTU KATA BERMASALAH SISWA KELAS II MI - Irma Nurmalasari; Astri Sutisnawati; Din Azwar Uswatun (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to improve the early writing skills of second-grade students through the use of problematic word card manipulatives. The research employed a classroom action research design based on the Kemmis and McTaggart model, conducted in two cycles involving 18 second-grade students at MI Tegallame. The problematic word cards were designed as a medium for language error analysis, enabling students to identify, evaluate, and revise writing errors independently. Data were collected through writing tests and classroom observations. The results showed a significant improvement in students’ writing skills, with average scores increasing from 47.78 in the pre-cycle stage to 67.22 in Cycle I and 82.50 in Cycle II. Learning mastery also increased, reaching 82.50% in Cycle II. These findings indicate that problematic word card manipulatives effectively enhance early writing skills through an analytical learning approach that emphasizes students’ active cognitive engagement in the writing process.